Transforming growth factor-β impairs glucocorticoid activity in the A549 lung adenocarcinoma cell line - Salem, S.; Harris, T.; Mok, S.L.; Li, M.Y.; Keenan, C.R.; Schuliga, M.J.; Stewart, A.G. (2012)
Background and purpose.  The lung adenocarcinoma cell line, A549, undergoes epithelial mesenchymal cell transition (EMT) in response to transforming growth factor-β (TGF-β). Glucocorticoids did not prevent the EMT response, but TGF-β induced resistance to the cytokine-regulatory action of glucocorticoids. We sought to characterise the impairment of glucocorticoid response in A549 cells. Experimental approach.  A549 cells were exposed to TGF-β for up to 96 h before glucocorticoid treatment and challenge with IL-1α to ascertain the extent of glucocorticoid regulation of interleukin-6 (IL-6) and CXCL8 production. Nuclear localisation of glucocorticoid receptor (GR) α was ascertained by immunofluorescence and Western blotting. Glucocorticoid-response element (GRE) transactivation was measured with a transfected GRE-SEAP reporter. Key Results.  TGF-β (40-400 pM) reduced the maximum inhibitory effect of dexamethasone on IL-1α-induced IL-6 and CXCL8 production. The impaired glucocorticoid response was detected with 4 h of TGF-β (40 pM) exposure (and 4 h IL-1α to induce CXCL8 expression) and therefore was not secondary to EMT, a process that requires longer incubation periods and higher concentrations of TGF-β. TGF-β also impaired dexamethasone regulation of granulocyte-macrophage colony-stimulating factor in thrombin-stimulated BEAS-2B epithelial cells. Impaired regulation of CXCL8 was associated with markedly reduced GRE transactivation and reduced induction of IκBα mRNA, glucocorticoid-inducible leucine zipper (GILZ) and the epithelial sodium channel (SCNN1A). The expression, cellular levels and nuclear localisation of glucocorticoid receptor α were reduced by TGF-β. Conclusions and Implications.  We have identified that TGF-β impairs glucocorticoid responses in the A549 and BEAS-2B cell lines. © 2012 The Authors. British Journal of Pharmacology © 2012 The British Pharmacological Society.